Correlation between periodontal status of maxillary molars and maxillary sinus mucosal thickening - SONG Yujiao, SUN Xiaojun (口腔疾病防治)
Objective To investigate the effect of periodontal inflammation of maxillary molars on the mucosal thickening of the maxillary sinus and to provide references for the prevention and treatment of odontogenic maxillary sinusitis. Methods This study was approved by the hospital’s Medical Ethics committee. A retrospective analysis was conducted on the cone beam CT (CBCT) images of the maxillary sinuses of 246 patients with periodontitis. Based on the inclusion and exclusion criteria, a total of 331 maxillary sinus images were finally included. The molars with the most severe periodontal inflammation were selected for statistical analysis, including 270 first molars and 61 second molars. CBCT images of these patients were collected. Periodontal indices of maxillary molars [minimum remaining alveolar bone height (minRABH), degree of alveolar bone absorption, furcation involvement, and vertical bone loss] were measured. The correlation between these periodontal indices and maxillary sinus mucosal thickening (defined as normal when the maximum thickness of the maxillary sinus mucosa ≤ 2 mm and thickening when>2 mm) was analyzed. Results Among the 331 maxillary molars and their corresponding maxillary sinuses, 264 cases showed thickening of the maxillary sinus mucosa, with an average thickness of (5.9 ± 5.1) mm, accounting for 79.8%. The thickening of the maxillary sinus mucosa was significantly correlated with periodontal indices, including minRABH, degree of alveolar bone absorption, furcation involvement, and vertical bone loss (P<0.05), as well as with tooth position (P<0.05). Further binary logistic regression analysis revealed that the possibility of maxillary sinus mucosal thickening in the minRABH<4 mm group was 5.6 times that of the group with minRABH ≥ 10 mm. The possibility of maxillary sinus mucosal thickening in the group with minRABH of 4-10 mm was 2.2 times that of the group with minRABH ≥ 10 mm. The possibility of maxillary sinus mucosal thickening caused by periodontitis in the second maxillary molar was 2.8 times that of the first maxillary molar. minRABH and tooth position of the maxillary molar had a more significant impact on the thickening of the maxillary sinus mucosa compared to other factors (P<0.05). Conclusion When the minRABH of maxillary molars is less than 4 mm or when the tooth position is the second maxillary molar, the possibility of thickening of the maxillary sinus mucosa increases. This suggests that thorough periodontal treatment is an important factor in preventing odontogenic maxillary sinusitis.